Movimiento caótico de partículas libres que viajan sobre guías de ondas bajo un potencial eléctrico apantallado - Moya Egoavil y Cols., C. (2019)
The study of chaotic behavior in the dispersal and movement presented by free particles shielded against potential within half mesoscopic waveguide, we performed the analysis of the dimensionless Hamiltonian function retain workers in conjugate coordinates, representing and evaluating state trajectories in phase space with a topological path at fixed points of Poincare characteristic of the system, the origin x = 0 and x = ±∞, and its stability as a nonlinear dynamic system using the Hamilton equations of motion . By numerical analysis portrayed the autonomous function of Hamilton conservative nonintegrable due to potential perturbation within the system was applied, giving information to Stripper Arm the system was unstable and the orbits drawn by the state space, tend to asymptotic behavior on a characteristic point at x = 0, away from them there is no predictability of the development space for these particles, this means a smaller scale chaos to describe physical movement.